Symptom Severity at Week 4 of Cognitive-Behavior Therapy Predicts Depression Remission. Issue 4 (July 2019) - Persons, Jacqueline B.; Thomas, Cannon
Abstract: Early response has been shown to predict psychotherapy outcome. We examined the strength of the relationship between early response and remission in 82 patients who received naturalistic cognitive-behavior therapy in a private practice setting, and 158 patients who received protocol cognitive therapy in a research setting. We predicted that the relationship between early response and remission would be substantial enough to guide clinical decision making in both samples, and that a simple model of severity at Week 4 of treatment would predict remission as effectively as a more complex change score. Logistic regressions showed that a simple model based on the Week 4 Beck Depression Inventory (BDI) score was as predictive of remission as more complex models of early change. A receiver operating characteristics analysis showed that BDI score at Week 4 was substantially predictive of remission in both the naturalistic and research protocol samples; the area under the curve was .80 and .84 in the naturalistic and protocol samples, respectively. To guide clinical decision making, we identified threshold scores on the BDI corresponding to various negative predictive values (probability of nonremission when nonremission is predicted). Our results indicate that depressed patients who remain severely depressed at Week 4 of cognitive therapy are unlikely to reach remission at the end of relatively brief (maximum 20 sessions) treatment. We discuss implications of our findings for clinical decision making and treatment development. Highlights: Depression severity after 4 weeks of CBT is a substantial predictor of remission. Severity at Ssession 5 is an equal or better predictor of remission than early response. Patients whose symptoms are severe at Session 5 are very unlikely to remit.